Peer review of the pesticide risk assessment of the active substance pethoxamid. (20th September 2017) - ,; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Bellisai, Giulia; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Byers, Harry; Chiusolo, Arianna; Court Marques, Daniele; Crivellente, Federica; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Austria, and co‐rapporteur Member State, the Czech Republic, for the pesticide active substance pethoxamid are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of pethoxamid as a herbicide on maize and soya bean. The reliable endpoints, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.